2009
DOI: 10.1109/tbme.2008.2011647
|View full text |Cite
|
Sign up to set email alerts
|

MR Measurement of Cerebrospinal Fluid Velocity Wave Speed in the Spinal Canal

Abstract: Noninvasive measurement of the speed with which the cerebrospinal fluid (CSF) velocity wave travels through the spinal canal is of interest as a potential indicator of CSF system pressure and compliance, both of which may play a role in the development of craniospinal diseases. However, measurement of CSF velocity wave speed (VWS) has eluded researchers primarily due to either a lack of access to CSF velocity measurements or poor temporal resolution. Here, we present a CSF VWS measurement methodology using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 11 publications
4
35
1
Order By: Relevance
“…For entry into ADINA, these viscoelastic properties were translated into equivalent values of viscoelastic shear and bulk moduli. These choices gave significant energy dissipation and a principal wavespeed of slightly over 7 m s À1 , comparable with what has been measured using magnetic resonance imaging in vivo for the spinal cord (Kalata et al, 2009). The cord properties were maintained unchanged as the crosssection tapered inwards at the caudal end, but the ligamentous filum terminale was given the same properties as the dura.…”
Section: Article In Presssupporting
confidence: 62%
“…For entry into ADINA, these viscoelastic properties were translated into equivalent values of viscoelastic shear and bulk moduli. These choices gave significant energy dissipation and a principal wavespeed of slightly over 7 m s À1 , comparable with what has been measured using magnetic resonance imaging in vivo for the spinal cord (Kalata et al, 2009). The cord properties were maintained unchanged as the crosssection tapered inwards at the caudal end, but the ligamentous filum terminale was given the same properties as the dura.…”
Section: Article In Presssupporting
confidence: 62%
“…The speeds of the two waves can be calculated as eigenvalues of the governing system of equations (3) [26]; for the parameters used in the model they amount to roughly 7 and 14 m/s, which is consistent with the estimates from the in vivo measurements [35]. Given the length of the spinal column, this means that only the inputs of several Hz or higher can lead to wave-type behaviour in the spinal CSF.…”
Section: Discussionsupporting
confidence: 67%
“…This value matches other published values of wave speeds in the spinal canal. A summary of six independent studies of wave speed measurements was recently published by Kalata et al 25 Half of the studies reported a wave speed in the spinal canal of about 4 m/s. As discussed by these authors, in studies reporting values higher than 4 m/s there may have been significant experimental errors.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers claim that the pressure wave speed in the spinal canal may be an indicator of pathological changes in the CNS. 9,18,25 The wave speed was calculated by first noting the time at which peak pressures occur in three different locations of the spinal canal. Figure 9 shows that the peak pressure in the upper region occurs at 2% of the cardiac cycle and that peak pressures in the middle and lower regions occur at 4 and 22%, respectively.…”
Section: Detailed Pressure Predictions In the Spinal Canalmentioning
confidence: 99%